1996
DOI: 10.1111/j.1745-6584.1996.tb02172.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Aperture Measurements and Migration of Solutes, Viruses, and Immiscible Creosote in a Column of Clay‐Rich Till

Abstract: A series of ground‐water flow and tracer experiments were performed on an undisturbed column of fractured clay‐rich till, 0.5 m diameter by 0.5 m long, in a pressure‐controlled cell. The measured hydraulic conductivity of the sample was 1.0 to 1.2 × 10–6 m/sec and the average hydraulic gradient during the tracer experiments ranged from 0.45 to 0.49. The experiments clearly show that ground‐water flow and contaminant migration through the sample is primarily controlled by fractures and root holes. Tracer experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 15 publications
6
51
1
Order By: Relevance
“…A test performed [Hinsby et al, 1996] showed that the conductivity meter measurements could be directly correlated with the breakthrough of chloride (measured by specific analyses). Recorded effluent conductivities (e e) were normalized (e * ) to influent conductivities (e i) with the expression e * = (ee --e background) / (ei -e background)' Influent and effluent p H were measured using a Radiometer oe H meter.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…A test performed [Hinsby et al, 1996] showed that the conductivity meter measurements could be directly correlated with the breakthrough of chloride (measured by specific analyses). Recorded effluent conductivities (e e) were normalized (e * ) to influent conductivities (e i) with the expression e * = (ee --e background) / (ei -e background)' Influent and effluent p H were measured using a Radiometer oe H meter.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Models have been developed for understanding flow through fractured heavily fractured clay horizons, using the hydraulic aperture approach (e.g. McKay et al 1999;Hinsby et al 1996 and references therein), although Jørgensen et al (1998) found that this approach did not predict DNAPL movement in column experiments. Although high numbers of biopores were discovered per square metre (see Fig.…”
Section: Biopores: Characteristics and Frequency Of Occurrencementioning
confidence: 99%
“…Douglas 1986;Driese et al 2001;McKay et al 1999McKay et al , 2005McKay and Fredericia 1995;Rodvang and Simpkins 2001;Rudolf et al 1991;Shaw and Hendry 1998) and the permeability with respect to contaminants such as coal tar and coal tar distillate polycyclic aromatic hydrocarbons (e.g. Hinsby et al 1996;Vulava et al 2007). Biopores are specifically holes that occur in soils/sediments due to plant growth and/or the action of animals earth worms (Oades 1993;Edwards et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, DNAPL often result in serious contamination problems (Pankow & Cherry 1996). The DNAPL are able to penetrate fractures with apertures of only a few micrometres relatively easy (Kueper & McWhorter 1991;Hinsby et al 1996;Pankow & Cherry 1996) and furthermore, due to their high densities, they are able to sink relatively deeply into the aquifers where they may contaminate old groundwaters (Bishop et aL 1993;Lawrence et al 1996;Pankow & Cherry 1996). DNAPL source zones are capable of contaminating very large amounts of groundwater with highly toxic components.…”
Section: Non-aqueous Phase Liquids (Napl)mentioning
confidence: 99%